2011
DOI: 10.1038/ng.1009
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3a is essential for hematopoietic stem cell differentiation

Abstract: Loss of the de novo DNA methyltransferases Dnmt3a and Dnmt3b in embryonic stem cells obstructs differentiation; however, the role of these enzymes in somatic stem cells is largely unknown. Using conditional ablation, we show that Dnmt3a loss progressively impairs hematopoietic stem cell (HSC) differentiation over serial transplantation, while simultaneously expanding HSC numbers in the bone marrow. Dnmt3a-null HSCs show both increased and decreased methylation at distinct loci, including substantial CpG island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
606
4
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 945 publications
(669 citation statements)
references
References 47 publications
(60 reference statements)
38
606
4
4
Order By: Relevance
“…7B). Consistent with the published observation that dif- (4,24,25), we found that an intergenic region in the proximity of the Iqgap2 locus was substantially hypomethylated in KO cells (Fig. 7B).…”
Section: Dysregulated Dna Methylation Activity Leads To Increased Massupporting
confidence: 81%
See 2 more Smart Citations
“…7B). Consistent with the published observation that dif- (4,24,25), we found that an intergenic region in the proximity of the Iqgap2 locus was substantially hypomethylated in KO cells (Fig. 7B).…”
Section: Dysregulated Dna Methylation Activity Leads To Increased Massupporting
confidence: 81%
“…S1D). Second, the differentially methylated regions identified in Dnmt3a-null cells showed substantial hyper-as well as hypomethylation at a variety of genomic regions, with very little correlation between changes in methylation and differential gene expression in the absence of Dnmt3a in both mouse and human cells (4,24,25). These observations suggest the existence of both direct and indirect effects due to the loss of Dnmt3a, and potentially also the existence of DNMT3A activities that are independent of its DNA catalytic activity (26), similar to what has been described for the catalytically inactive DNMT3L (27), some of the DNMT3B isoforms (28), and even for the TET family of DNA-modifying enzymes (29,30).…”
Section: Dysregulated Dna Methylation Activity Leads To Increased Masmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful genotypephenotype correlations suggest that patients manifest DNMT3A mutations in preleukemic hematopoietic stem cells (HSCs)/multipotent progenitors (MPPs), which exhibit a competitive advantage over normal HSCs. Because these mutations occur at a very early stage among genetic abnormalities, they are likely involved in the development of leukemia (7,8).Functionally, the DNMT3A R882 mutation might disrupt epigenetic regulation. This kind of DNMT3A mutation confers reduced methyltransferase activity and promotes the possibility of dominant-negative consequences compared with the wild-type (WT) allele (2, 9, 10).…”
mentioning
confidence: 99%
“…There is considerable heterogeneity in genetic mutations among patients with MDS that may explain the diversity of clinical presentations that differ in the numbers and depths of cytopenias, risks toward progression to acute myeloid leukemia (AML), responses to treatment, and survival times [5][6][7][8]. Gene mutations affecting epigenetic chemical modifications, such as mutations in TET2 and DNMT3A, are among the most common in MDS [9][10][11].…”
Section: Introductionmentioning
confidence: 99%